Acute Kidney Injury Induced by Systemic Inflammatory Response Syndrome is an Avid and Persistent Sodium-Retaining State - Daniel Vitorio; Alexandre Toledo Maciel (Case Reports in Critical Care)
Acute kidney injury (AKI) is a frequent complication of the systemic inflammatory response syndrome (SIRS), which is triggered by many conditions in the intensive care unit, including different types of circulatory shock. One under-recognized characteristic of the SIRS-induced AKI is its avidity for sodium retention, with progressive decreases in urinary sodium concentration (NaU) and its fractional excretion (FENa). This phenomenon occurs in parallel with increases in serum creatinine, being only transitorily mitigated by diuretic use. In the present case, we report a situation of two consecutive shocks: the first shock is hemorrhagic in origin and then the second shock is a septic one in the same patient. The SIRS and AKI triggered by the first shock were not completely solved when the second shock occurred. This could be viewed as a persistent avid sodium-retaining state, which may be appreciated even during renal replacement therapy (in the absence of complete anuria) and that usually solves only after complete AKI and SIRS resolution. We suggest that decreases in NaU and FENa are major characteristics of SIRS-induced AKI, irrespective of the primary cause, and may serve as additional monitoring tools in its development and resolution.